High-resolution manometry in diagnostics and evaluation of therapy effectiveness in patients with eosinophilic esophagitis – underestimated breakthrough or dead end? - Joanna A. Sarbinowska (Gastroenterology Review, 2019)
Eosinophilic esophagitis (EoE) is a chronic disease with non-specific symptoms, among which dysphagia is a prevailing one. The observed increase of EoE rate, its chronic and recurrent character, as well as invasive follow-up examination (periodical panendoscopy with specimen collection for histopathology), compel optimization of both the diagnostics algorithm and disease monitoring through searching for new, unique methods and tools so far not applied, including high-resolution manometry (HRM). Mentioned investigations result from advances in comprehension of disease pathogenesis, in which it is suggested that development of a chronic inflammatory reaction of the esophageal wall may lead to consecutive fibrosis and motility disorders. In research published to date one manometric pattern characteristic for EoE was not obtained, whereas the obtained inconsistent and at times contradictory results do not correlate either with symptoms exacerbation or endoscopic scan. Numerous constraints of discussed studies as well as current knowledge in disease etiopathology and esophagus biomechanics prompt further investigation of HRM significance in diagnostics and therapy monitoring of patients with EoE.